The Lim family in the politics of Tibiao - Calawag, Jelvet Amor E.
This research documents and explains the emergence and persistence of the Lim family in the politics of Tibiao. Through interviews and archival research, the study reveals that even before any member of the Lim family entered the politics, they were already one of the prominent families in Tibiao. Their evolution as politicians could be traced back to an ancestor as early as 1919. They become well known and strong in local politics because of their rich political resources (including land, fiancial capability, human capabilities), their prestigious and historic name and the support of big politicians and other relatives. Their activities and philantrophic deeds as politicians enhanced their family's image; They are highly regarded, respected and trusted by the people. It is concluded that the family maintains their dominance in electoral politics by manifesting their concern to the people using government resources and utilizing their political resources.